Traumatic Experiences, Revictimization and Posttraumatic Stress Disorder in German Inpatients Treated for Alcohol Dependence. (21st March 2018) - Grundmann, Johanna; Lincoln, Tania M.; Lüdecke, Daniel; Bong, Sönke; Schulte, Bernd; Verthein, Uwe; Schäfer, Ingo
ABSTRACT: Background : Traumatic experiences and posttraumatic stress disorder (PTSD) are prevalent in patients with alcohol use disorders (AUDs) and affect its course and outcome. Prior prevalence reports are limited by the inclusion of individuals with additional substance use disorders (SUDs), a focus on childhood events only and the use of self-ratings only. Objectives : To examine the prevalence of traumatic experiences, revictimization and PTSD in inpatients treated for alcohol dependence without other SUD, emphasizing interpersonal violence across the whole lifespan. Methods : For this cross-sectional study alcohol-dependent patients without additional SUD ( N = 230, 73% male, mean age 43 years) were recruited in an inpatient detoxification unit and were administered the Structured Trauma Interview, the Posttraumatic Diagnostic Scale, and the Structured Clinical Interview for DSM-IV. Data analysis comprised descriptive statistics and appropriate significance tests. Results : 36.2% reported severe childhood physical or sexual abuse and 45.6% reported at least one of these types of abuse in adulthood. The lifetime rate of interpersonal violence was 61.1%. The prevalence of current PTSD was 13.2%. Women with a history of childhood abuse were about seven times as likely to be victimized in adulthood as women without these experiences, while in men revictimization was not significant. Conclusions : Even in patients with alcohol dependence without additional SUD experiences of interpersonal violence and PTSD are frequent. In order to adequately respond to the needs of this population, trauma and PTSD should routinely be assessed in alcohol-dependence treatment and considered in treatment planning if necessary.